THE IMPACT OF ALTERNATIVE SCHOOLS ON SOCIETY AND NATION - Mohd Shahrizal bin Timhar; Nuraisa binti Lakiramang; Muhammad Wildanun Johrin bin Ependi; Yustang bin Waris, (Malaysian Journal of Business and Economics (MJBE), 2021)
Alternative schools are established to provide education to a group of people who are marginalized from the national education system due to several factors such as economic, political and social. Alternative schools are also educational environments designed to cater to the educational needs of especially those from poor communities and refugees from neighbouring countries. The main purpose of this study is to explore the impact of alternative schools on society and the country. Nevertheless, the objective of this study is to determine whether the alternative schools can help in eradicating illiteracy in the community, to estimate whether the alternative school can alleviate social problems and to analyse whether schools can form a virtuous personality in every student. The independent variables are illiteracy eradication in the community, alleviation of social problems, and virtuous personality while the dependent variable is the perception of the impact of alternative schools on society and the nation. The questionnaire was converted into Google form and distributed in several Alternative Schools including Cahaya Society, Teratak Mahasiswa and Borneo Komrad where all three schools are located in Sabah. A total of 60 respondents answered and completed the questionnaire. The response was analysed after passing the reliability and the validity test. The hypothesis of the study was further analysed using inferential statistics, regression analysis. The result revealed that the Alternative Schools can eradicate poverty, alleviate social problems and for a virtuous personality among the students.